RELATION SHIP FISHING TRIP, SIZE OF THE SHIP.SIZE OF THE MACHINE AND THE MACHINE AGE TO THE AMOUNT OF FUEL CARRIED FISH NET IN THE OCEAN FISHING PORT BELAWAN. - Hutabarat, Rinova; Zain, Jonny; ', Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in 17-31 March 2015 in the oceanfishing portBelawan. This goal to find the amount offuelthatmustbe brought a fish net fishing board when performing fishing effort. Data could be gotten by research to 27 samples of fish net merk is Cummins machine. Seeing the relationshipfishing trip, size of theship, size of the machine and machine age to theamount offuelcarried fish net use statistics multiple regression analysis. Basedtestinganddiscussionin this research was capable of concluding that fishing trip (X1), size of the ship (X2), and themachine age (X3) to amount offuel that carried by fisherman (Y) is Y= 27,548+0,20X1-1,549X2+0,01X3. The percentage of independent variables to dependent variables is77%.Keywords: Fishing trip, machine, fishing board